Mirando la voz (a)callada: dimensiones del silencio en El miedo y Decir sí, de Griselda Gambaro - Santana, Lucía G. (Latin American Theatre Review, 2013)
This article undertakes the contrastive analysis of two of Griselda Gambaro´s absurdist plays of the seventies, El miedo and Decir sí, which exemplify the relationship between the different dimensions of textual and extra-textual silence as the grounds of the author´s ethic-aesthetic activism. Objects in space, visuality, and intertextuality establish a correspondence between textual silence and the different dimensions of State silence that become the main tool for sociopolitical subjection by repressive regimes. Thus, it brings light onto the spectacular strategies used for the control of the symbolic order, providing the audience with new resources to deconstruct hegemonic discourses without incurring in the violence that it wants to denounce.